THE STRUGA HALVETİ LODGE IN NORTH MACEDONİA: AN ANALYSİS OF ITS RELİGİOUS PRACTİCES İN TERMS OF MUSİC, LANGUAGE, AND IDENTİTY (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The Balkans became a significant center of Turkish culture beginning in the 13th century with the settlement of Oghuz Turks migrating from Anatolia. The language, culture, religion, and music carried into the region by the Turks continue to be represented today. North Macedonia is one of the Balkan homelands where both Sunni and Bektashi interpretations of Turkish-Islamic tradition are present, and the relationship of these traditions with music remains a valuable source for musicological inquiry. The Halveti order, an Islamic Sufi order that emerged in Baku in the 14th century, spread across Anatolia and the Balkans. It later gained a following not only among the Turkish population but also among Muslim Albanians and Torbeš communities in cities such as Ohrid, Kičevo, and Struga. This study focuses specifically on the religious practices observed at the Struga Halveti Lodge, one of the active Halveti institutions in North Macedonia. Religious music, which occupies a vast corpus within the broader framework of Turkish music, is categorized under separate headings based on its performance contexts in mosques and Sufi lodges. The musical structures accompanying the religious practices at the still-active Struga Halveti Lodge are examined and interpreted in relation to language, identity, ethnicity, and cultural interaction. The study further explores concepts such as the migration of music, claims of multiple identities, and performative ownership. It offers a comparative sociological analysis of Halvetism and Bektashism— seen here as differing interpretations of Turkishslamic traditions—particularly within the context of Macedonia, using categories such as urban and rural religious expression. The findings and observations presented in this article are primarily based on data collected during fieldwork conducted in 2022.
Keywords: Turkishness in the Balkans, Halveti Order, Music, Bektashism, Religious Music